Carotenoid and chlorophyll profiles in five species of Malaysian seaweed as potential Halal Active Pharmaceutical Ingredient (API) - Othman, Rashidi; Md Amin, Nur Alifah; Abdullah Sani, Muhammad Shirwan; Ahmad Fadzillah, Nurrulhidayah; Jamaludin, Mohd Aizat (Indonesian Society for Knowledge and Human Development (INSIGHT), 2018)
Seaweed, also known as macroalgae, consist of various species that have been gaining the interest of researchers due to the presence of functional bioactive compounds that can be extracted from their biomass. This research aimed to study the chlorophyll and carotenoid content from five species of Malaysian seaweed as potential Active Pharmaceutical Ingredient (API). Three species of red macroalgae, (Eucheuma denticulatum, Gracilaria tikvahiae, and Kappaphycus striatum), green macroalgae (Caulerpa lentillifera ) and one brown macroalga (Padina pavonica) were selected and their chlorophyll and carotenoid contents were determined by using UV-Vis spectrophotometer and HPLC. Their antioxidant and antimicrobial activities were investigated using DPPH Radical Scavenging activity and Disc Diffusion methods, respectively. In terms of carotenoid content, P. pavonica contained the highest amount of carotenoid (100.9 ± 14.7 ug/g DW) and chlorophyll content (7.5 ±1.5 ug/g DW). Meanwhile, based on individual carotenoid content, K. striatum had the highest lutein content (38.6 ug/g DW). Zeaxanthin, beta-carotene, and violaxanthin were significantly higher in C. lentillifera at 21.3 ug/g DW, 10.7 ug/g DW, and 8.9 ug/g DW respectively. Besides that, the antioxidant test showed that P. pavonica presented the strongest DPPH activity with the percentage of inhibition (I %) of (61.0 % ± 0.9). Finally, for the antimicrobial test, strong antimicrobial activities were shown by all the seaweed samples toward E. coli and P. aerugenosa. Overall results of the antifungal test demonstrated moderate antifungal action by all seaweed samples towards M. gypseum and Fusarium sp.